Initial growth of four tree species at different spacings - Caron, Braulio Otomar (2020)
The objective of this paper was to evaluate the initial increase of the height and diameter of the collum of the species Acacia mearnsii De Willd, Eucalyptus grandis Hill, Mimosa scabrella Benth and Ateleia glazioviana Baill in the spacings 2 x 1m; 2 x 1.5m; 3 x 1m and 3 x 1.5m, with views to the production of wood for energy in cultures of short rotation. An experimental design of randomized blocks was used in a factorial outline of 4 x 4. The evaluations were accomplished in the periods 0, 60 and 120 days after the planting of the seedlings in the field. In the initial periods there was interference of the spacing in the diameter of collum of the species A. mearnsii and in the height of the species E. grandis. The initial growth in height of the species M. scabrella (122.1cm) and E. grandis (97.2cm) was higher than those of A. mearnsii (70.9cm) and A. glazioviana (26.7cm) after 120 days of the planting of the seedlings in the field.